2019
DOI: 10.21577/0103-5053.20190073
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Different Ammonium Cations on the Optical Properties of Tetrakis GdIII and EuIII Complexes

Abstract: A series of tetrakis-b-diketonate Q + [Ln(b-dik) 4 ]-, where Ln = Gd III or Eu III , Q = ammonium cations and b-dik = tta (2-thenoyltrifluoracetone) or bmdm (1-(4-tert-butylphenyl)-3-(4-methoxyphenyl)-1,3-propanedione) have been synthesized and characterized. The environment surrounding the Eu III ion depends on the lateral groups of the ligand and on the alkyl chains of the counter ion Q. The shortest lifetime (τ) = 0.29 ms, and lowest quantum efficiencies (η) = 24%, were obtained for (N(C 12 H 25) 2 (CH 3) 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 49 publications
0
8
0
2
Order By: Relevance
“…The nature of the cations in [Eu(β-diketonate) 4 ] − -based salts can have a strong influence on the structure of the anion and consequently on the optical properties of the complexes [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The nature of the cations in [Eu(β-diketonate) 4 ] − -based salts can have a strong influence on the structure of the anion and consequently on the optical properties of the complexes [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…For the [P 6,6,6,14 ][Eu(FOD) 4 ] ionic liquid, it was observed a gradual colour change from the familiar light yellow to a deep red at temperatures close to 80 °C, attributed to partial β‐diketonate decomplexation, with concomitant establishment of a strong anion‐cation interaction . Additionally, it was also reported that the cations of [Eu(β‐diketonate) 4 ] salts can have a strong influence on the structure of the anion and consequently on the optical properties of the complexes . For complex 1 , the temperature perturbation affected the coordinating ligand, lowering its excitation energy, thus shifting the excitation spectra closer to the visible region in 10 nm.…”
Section: Resultsmentioning
confidence: 99%
“…При расчёте большинства параметров по спектрам излучения соединений Eu 3+ в в последние два десятилетия использовалась регистрация излучаемой мощности, в то время как большинство современного оборудования позволяет определять количество излучаемых фотонов в секунду [35][36][37][38][39][40][41][42]. Кроме того, все оценки параметров интенсивности, интегральных интенсивностей и центроидов получали при использовании спектров излучения, записанных в длинах волн.…”
Section: Introductionunclassified